2020
DOI: 10.1016/j.jinf.2020.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Differential immune activation profile of SARS-CoV-2 and SARS-CoV infection in human lung and intestinal cells: Implications for treatment with IFN-β and IFN inducer

Abstract: Objectives: Respiratory and intestinal tract are two primary target organs of SARS-CoV-2 infection. However, detailed characterization of the host-virus interplay in infected human lung and intestinal epithelial cells is lacking. Methods: We utilized immunofluorescence assays, flow cytometry, and RT-qPCR to delineate the virological features and the innate immune response of the host cells against SARS-CoV-2 infection in two prototype human cell lines representing the human lung (Calu3) and intestinal (Caco2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 50 publications
10
59
0
Order By: Relevance
“…An intriguing finding from this study is that while ILRUN regulates the type I IFN induction pathway, SARS-CoV-2 did not induce a noticeable type I IFN response in Caco-2 cells, indicating this is independent of the ILRUN-induced IFN expression. Another study has similarly observed a lack of type I IFN induction in Caco-2 cells infected with SARS-CoV-2, including at a high MOI (38). While one explanation for this result is that Caco-2 cells do not mount robust innate immune response to viral infection, previous studies have shown infection of Caco-2 cells with Sendai virus and Newcastle Disease virus induces a strong type I IFN response, while SARS-CoV-1 suppresses these cytokines (39).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…An intriguing finding from this study is that while ILRUN regulates the type I IFN induction pathway, SARS-CoV-2 did not induce a noticeable type I IFN response in Caco-2 cells, indicating this is independent of the ILRUN-induced IFN expression. Another study has similarly observed a lack of type I IFN induction in Caco-2 cells infected with SARS-CoV-2, including at a high MOI (38). While one explanation for this result is that Caco-2 cells do not mount robust innate immune response to viral infection, previous studies have shown infection of Caco-2 cells with Sendai virus and Newcastle Disease virus induces a strong type I IFN response, while SARS-CoV-1 suppresses these cytokines (39).…”
Section: Discussionmentioning
confidence: 90%
“…SARS-CoV-2 appears to be particularly adept at immune evasion, encoding seven proteins that inhibit IFN-β promoter activation (43), among them the ORF6 protein that blocks both type I IFN induction and signalling pathways. Several groups have hypothesized that the lack of timely and robust antiviral response to SARS-CoV-2 infection contributes to COVID-19 pathogenesis (38, 43).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that SCFAs can also have systemic effects, which may be relevant for SARS-CoV-2 infection in different contexts. 31 …”
Section: Discussionmentioning
confidence: 99%
“…This has been confirmed in Calu3 cells, primary human airway epithelial cells (pHAE), alveolar epithelial type 2 cells (AT2s), A549 lung alveolar cells and in a reconstituted human bronchial epithelium model (MucilAir ™ model), where SARS-CoV-2 infection failed to induce an appropriate type I and III IFN response (Blanco-Melo et al, 2020;Huang et al, 2020;Robinot et al, 2020;Shuai et al, 2020;Vanderheiden et al, 2020). According to recent reports, COVID-19 also causes an impaired type I IFN response in the periphery.…”
Section: Covid-19 Patients Show a Delayed Type I Interferon Responsementioning
confidence: 67%